A Review of Cassava Supply Chain Performance Improvement: A Case of Cassava Supply Chain in Thailand - Anothai Xanthavanij; Sataporn Amornsawadwatana (International Journal of Supply Chain Management, 2019)
The purpose of this study is to review the previous studies on the supply chain management (SCM) contexts by applying to the cassava supply chain, and focuses on the case study in Thailand with the objective to the improve the performance of the supply chain. Literature reviews on the previous SCM contexts have been undertaken a thorough search of articles on selected journals relevant to SCM and cassava supply chain during the past 20 years (1998-2018). This paper aimed to provide information about the cassava supply chain, and use SCM contexts to improve the supply chain performance in order to sustain the competitive advantage to the future.